Extended-spectrum β-lactamase- and pAmpC-producing Enterobacteriaceae among the general population in a livestock-dense area. (February 2017) - Wielders, C.C.H.; van Hoek, A.H.A.M.; Hengeveld, P.D.; Veenman, C.; Dierikx, C.M.; Zomer, T.P.; Smit, L.A.M.; van der Hoek, W.; Heederik, D.J.; de Greeff, S.C.; Maassen, C.B.M.; van Duijkeren, E.
Abstract: Objectives: In the Netherlands there is an ongoing debate regarding environmental health risks of livestock farming for neighbouring residents. This explorative study aims to determine the prevalence of carriage of extended-spectrum β-lactamase and/or plasmid-mediated AmpC-producing Enterobacteriaceae (ESBL/pAmpC-E) in the general population living in a livestock-dense area, and to study associations between determinants, including exposure through contact with animals and the environment, and human carriage of ESBL/pAmpC-E. Methods: A cross-sectional study was performed among 2432 adults (aged 20–72 years) in 12 temporary research centres in the south of the Netherlands, consisting of a questionnaire and analysis of a faecal sample to assess carriage of ESBL/pAmpC-E. Risk factors were analysed using logistic regression. Results: The prevalence for carriage of ESBL/pAmpC-E was 4.5% (109/2432; 95% CI 3.7–5.4) ranging from 1.4% to 10.9% among the research centres. ESBL/pAmpC resistance genes were detected in Escherichia coli and Klebsiella pneumoniae isolates obtained from these 109 persons and the most common ESBL-resistance genes were bla CTX-M-15, bla CTX-M-14/17 and bla CTX-M-1, originating from 76 participants. Travel in the previous 12 months to Africa, Asia or Latin America (OR 2.82; 95% CI 1.71–4.63), having kept cows for a hobby in the previous 5 years (OR 3.77; 95% CI 1.22–11.64), usage of proton-pump inhibitors (OR 1.84; 95% CI 1.05–3.23), and living within 1000 m of a mink farm (OR 2.26; 95% CI 1.28–3.98) were identified as risk factors. Exposure to poultry was not identified as a risk factor. Conclusions: Overall, living in close proximity to livestock animals and farms does not seem to be a risk factor for carriage of ESBL/pAmpC-E.